Handbook of Research on Information Technology Management and Clinical Data Administration in Healthcare 2009
DOI: 10.4018/978-1-60566-356-2.ch017
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Interactive Voice Response Systems to Improve the Quality and Safety of Ambulatory Care

Abstract: This chapter highlights how an interactive voice response system (IVRS) may be used to improve quality of care problems associated with ambulatory care. The authors provide examples of quality problems, related to access, effectiveness, and safety, and describe how an IVRS may be used to reduce them. The chapter is also comprised of a comprehensive examination of published literature describing studies that have used IVRS interventions. The majority of these studies used an IVRS to manage patients with chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…16,17,[69][70][71]73,77 Two reviews reported improved educational outcomes 11,73 and seven reported significant positive behavioural change, 11,17,20,68,71,73,75 particularly improved self-monitoring or management in patients with diabetes 17 and better treatment adherence. 17,20,68 There were few firm conclusions about the impact of telehealth on quality of life, although one meta-analysis reported improvements associated with computer-mediated support groups. 75 The three reviews which suggested that telehealth improved social support 11,73,75 were countered by three that reported inconsistent or insufficient evidence.…”
Section: Specific Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17,[69][70][71]73,77 Two reviews reported improved educational outcomes 11,73 and seven reported significant positive behavioural change, 11,17,20,68,71,73,75 particularly improved self-monitoring or management in patients with diabetes 17 and better treatment adherence. 17,20,68 There were few firm conclusions about the impact of telehealth on quality of life, although one meta-analysis reported improvements associated with computer-mediated support groups. 75 The three reviews which suggested that telehealth improved social support 11,73,75 were countered by three that reported inconsistent or insufficient evidence.…”
Section: Specific Outcomesmentioning
confidence: 99%
“…70 However, other reviews showed limited impact on service utilisation 11,76 and meta-analyses reported that the evidence for a positive impact of telehealth on resource utilisation was questionable. 11,68,77 Cost-effectiveness Four reviews found some evidence for cost savings, 20,70,74,77 but one was unable to determine cost-effectiveness. 11 547 excluded as duplicates, not telehealth, not LTC focused, not systematic reviews, service-to-service interventions, protocols or conference proceedings 36 full papers retrieved for full-text screen by two reviewers 11 excluded: did not report outcomes, not LTC specific, historical accounts, service-to-service interventions, diagnosis specific 16 high-quality systematic reviews included in meta-review 25 systematic reviews assessed…”
Section: Specific Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these gaps, we designed an intervention using interactive voice response technology 911 to facilitate the delivery of evidence-based tobacco cessation counseling and medication after hospital discharge. The goal was to create a low-cost translatable system requiring minimal health system personnel to implement.…”
Section: Introductionmentioning
confidence: 99%
“…IVRS calls are increasingly used for drug monitoring posthospital discharge6 and they were shown to lower the costs of delivery of routine test results by 33% in comparison with inperson calls,7 and to facilitate treatment adherence 8 9. The IVRS can send automated calls at specific times, such as after the new prescription.…”
Section: Background and Significancementioning
confidence: 99%